2022
DOI: 10.3174/ajnr.a7389
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Collapse during Thrombectomy for Stroke: Clinical Evidence and Experimental Findings in Human Brains and In Vivo Models

Abstract: BACKGROUND AND PURPOSE: Aspiration thrombectomy has become a preferred approach to recanalize large-vessel occlusion in stroke with a growing trend toward using larger-bore catheters and stronger vacuum pumps. However, the mechanical response of the delicate cerebral arteries to aspiration force has not been evaluated. Here, we provide preclinical and clinical evidence of intracranial arterial collapse in aspiration thrombectomy. MATERIALS AND METHODS:We presented a clinical case of arterial collapse with prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…23 While we are enabled aspiration only at the moment before engagement, others have reported a successful version of this technique where aspiration is enabled for the entire intracranial catheter navigation. 24 This study has several limitations. First is the aforementioned selection bias because of the retrospective nature of the study.…”
Section: Discussionmentioning
confidence: 92%
“…23 While we are enabled aspiration only at the moment before engagement, others have reported a successful version of this technique where aspiration is enabled for the entire intracranial catheter navigation. 24 This study has several limitations. First is the aforementioned selection bias because of the retrospective nature of the study.…”
Section: Discussionmentioning
confidence: 92%
“…Counterbalancing the benefits of larger bore aspiration catheters is a concern for vessel injury. By using an in vivo rabbit model, Liu et al showed that due to the stronger vacuum forces of large bore catheters (such as 0.07 inch catheters), there is higher chance of arterial collapse during aspiration thrombectomy, which may theoretically result in absent flow and frictional arterial wall injury from the aspiration catheter 42. Likewise, while no significant overall association was found, subgroup analysis indicated that catheters with an ID ≥0.068 inch had a higher proportion of postprocedural intracranial hemorrhage compared with smaller catheters.…”
Section: Discussionmentioning
confidence: 99%
“…50 Catheters have also improved to better to determine safety and efficacy, particularly needed considering growing evidence for arterial collapse when a catheter is closer to vessel size. 53 Head-to-head clinical studies of specific devices are rare since next-generation devices are developed faster than completion of randomized controlled trials. Often, in vitro models are used to show superiority.…”
Section: Devicesmentioning
confidence: 99%